Clinical Epidemiological Study of Children with Cleft Lip and Palate - Shawana Iqbal, Shahab Adil, Syed Riaz Gillani, Syed Salman Shah, Asma Sami, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the frequency of different types of cleft lip and palate and to investigate the possible relation of some risk factors to cleft lip and palate. Study design: Descriptive study. Place and duration of study: Peshawar Dental College, Peshawar Pakistan from 1st August 2017 to 31st January 2019. Methodology: One hundred and seven patients with congenital cleft lip and cleft palate deformities, either gender and age ranged from 1 day to 720 days were enrolled. Cleft types were categorized as bilateral cleft lip and palate (BCLP), left cleft lip and palate (LCLP), right cleft lip and palate (RCLP), cleft alveolus (CLA) and bilateral incomplete cleft (BICLP). Results: There were 73(68.2%) males and 34(31.8%) females. The highest number of patients from Peshawar 30(28%) followed by Swat 21(19.8%) and Charssada by 11(10.3%). Forty two (39.3%) patients’ parents had consanguineous marriages. There were 89(83.2%) of mother haven't used folic acid during their pregnancy. Forty 40(37.4%) cases had a positive family history of cleft deformities. Most common systemic disease was anemia 25(23.2). Eighty five (79.4%) of cleft lip and palate patients were belonging to poor class family. Conclusion: The households of cleft lip and palate children demonstrated low socioeconomic status. The incidence of cleft lip and palate should be reduced to enhance the conditions of women during pregnancy by maintaining a balanced diet and giving them folic acid. Keywords: Epidemiology, Children, Cleft lip, Palate, Risk factors